Analisis Penerapan Coretax Dalam Pembuatan Faktur Pajak Pada PT. Dok Dan Perkapalan Kodja Bahari Tahun 2025 - Irsan Fathur Rahman; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2026)
The Coretax system is the latest innovation developed by the Directorate General of Taxes (DJP) as part of efforts to modernize tax administration, making it integrated, efficient, and digital-based. However, during its initial implementation, Coretax frequently experienced technical issues that caused delays in the issuance of tax invoices. This study aimed to conduct an in-depth analysis of the implementation of the Coretax system in the tax invoice issuance process at PT. Dok and Perkapalan Kodja Bahari. The research method used is a descriptive qualitative approach with data collection techniques used such as observation, in-depth interviews, and documentation. The results of the study indicated that the implementation of Coretax has a positive impact on the effectiveness of tax invoice administration, particularly in terms of issuance speed, data integration, and reporting transparency. However, there are still some challenges, such as users' lack of understanding of new features, inadequate technological infrastructure readiness, and frequent server outages in Coretax, which hinder and delay the tax invoice issuance process. Meanwhile, efforts to overcome these obstacles include internal training, intensive consultations, and improved technical coordination with various parties.